Modelling Medical Organizational Systems with Nets - Rothemund, M. (Methods of Information in Medicine, 1986)
In the medical area problems exist in documentation, in inter-personnel communication, in planning and consistently structuring medical organizational systems over the course of time. One possibility to moderate these problems seems to be the use of formal descriptive methods. Nets are selected as flexible tools fulfilling the demands made on such descriptive methods. In this article I suggest a technique for modelling medical organizational systems which is based on place/transition nets and predicate/transition nets.
Keywords: Petri Nets; Place/Transition Nets; Predicate/Transition Nets; Net Theory; Modelling of Systems; Medical Organizational Systems; Net Models; Organization